Investigation of Relationship between Occupational Stress and Cardiovascular Risk Factors among Nurses - Amin SABERINIA; Anna ABDOLSHAHI; Saeed KHALEGHI; Yaser MORADI; Hossein JAFARIZADEH; Ali SADEGHI MOGHADDAM; Mohsen AMINIZADEH; Mehdi RAEI; Alireza KHAMMAR; Mohsen POURSADEQIAN (Tehran University of Medical Sciences, 2020)
Background: One of the major causes of various work-related health problems among nurses is occupational stress. Hence, the main purpose of the present research was to find association between occupational stress of nurses and risk factors of cardiovascular disease. Methods:  In this cross-sectional study, the Osipow job stress questionnaire was employed to assess the occupational stress among the 250 nurses in Emam Khomeini hospital of Tehran in 2018. Based on stress score for participants, subjects divided into two groups: Scoring of group one was 60-179 (mild and average stress) and group two between 180 and 300 (average to acute and acute stress). Systolic and diastolic blood pressures were recorded for subjects after 10hrs fasting. Then the blood samples were collected to measure cholesterol, triglyceride and glucose levels. For determining the association between education level, job experience and study groups, the Chi-square test and for comparing job stress between two groups of study the Mann-Whitney U test was used. Results: Subjects with job stress in group one was 70(28%) and group two was 180(72%). The association between level of education and two study groups was not significant (P=0.129) while between job experience and two study groups was significant (P=0.004). Mean of Blood glucose levels for group I (98.0± 37.5), was higher than group II (82.5±12.0) and statistically significant (P=0.001). No significant difference was found between two groups of study for other parameters. Conclusion: High level of work-related stress among subjects affected the values related to blood glucose level, but no significant relationship was found between other risk factors of cardiovascular diseases and occupational stress among nurses.